2009
DOI: 10.1113/expphysiol.2008.046045
|View full text |Cite
|
Sign up to set email alerts
|

Iron injections in mice increase skeletal muscle iron content, induce oxidative stress and reduce exercise performance

Abstract: Iron accelerates the production of reactive oxygen species (ROS). Excessive levels of ROS are thought to accelerate skeletal muscle fatigue and contribute to the loss of skeletal muscle mass and function with age. Patients with an iron overload disease frequently report symptoms of weakness and fatigue, which is attributed to reduced cardiac function. The contribution of skeletal muscle to these symptoms is unknown. Using a mouse model of iron overload, we determined the extent of iron accumulation in skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 67 publications
6
68
6
Order By: Relevance
“…The highest muscle concentration occurred at 8 hours, 0.12 ± 0.02 mg Fe/cc, giving a peak tumor to peak non-tumor (surrounding muscle) ratio of 15.8. At 24 hours, the muscle content could not be distinguished from normal muscle iron content (0.068 mg Fe/cc 66 ), which would give a tumor to non-tumor ratio of .16.0 at 24 hours. Blood clearance exhibited a rapid early half-life of 2.0 hours followed by a slow component half-life of 14.0 hours.…”
Section: Resultsmentioning
confidence: 99%
“…The highest muscle concentration occurred at 8 hours, 0.12 ± 0.02 mg Fe/cc, giving a peak tumor to peak non-tumor (surrounding muscle) ratio of 15.8. At 24 hours, the muscle content could not be distinguished from normal muscle iron content (0.068 mg Fe/cc 66 ), which would give a tumor to non-tumor ratio of .16.0 at 24 hours. Blood clearance exhibited a rapid early half-life of 2.0 hours followed by a slow component half-life of 14.0 hours.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the elevation of oxidative stress was associated with the decreased functional capacity of muscle (Stefania et al, 2004) which also includes the decreased muscle endurance and muscle strength (Reardon and Allen, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in iron-treated mice showed an accumulation of this ion in soleus and EDL skeletal muscles, mainly in the ferritin light chain, which stocks iron; they also observed an increase of oxidative stress and antioxidant enzymes activity in these muscles (Reardon and Allen 2009). Rodriguez et al (2007) using microarray test, in which 47,000 probes were studied, have found that a small number of genes is altered in skeletal and cardiac muscle after iron overload, only those that, in some way, are involved in the metabolism of glucose and lipids.…”
Section: Resultsmentioning
confidence: 96%